2017
DOI: 10.1038/s41598-017-12780-y
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin promotes triacylglycerol accumulation via MT2 receptor during differentiation in bovine intramuscular preadipocytes

Abstract: Melatonin (N-acetyl-5-methoxytryptamine) is a derivative of tryptophan which is produced and secreted mainly by the pineal gland and regulates a variety of important central and peripheral actions. To examine the potential effects of melatonin on the proliferation and differentiation of bovine intramuscular preadipocytes (BIPs), BIPs were incubated with different concentrations of melatonin. Melatonin supplementation at 1 mM significantly increased peroxisome proliferator-activated receptor γ (PPARγ), CCAAT/en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 72 publications
2
26
0
Order By: Relevance
“…Ten mid‐lactating Holstein dairy cows with similar parity, lactating time, milk production, milk fat, and milk protein were randomly divided into a melatonin‐treated group and untreated group, each with 5 cows. Melatonin‐treated cows were given subcutaneous injections of 4.64 mg melatonin (Sigma) for four consecutive days at 8:00 am based on previous study . Five control cows received the vehicle (absolute ethyl alcohol) only.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ten mid‐lactating Holstein dairy cows with similar parity, lactating time, milk production, milk fat, and milk protein were randomly divided into a melatonin‐treated group and untreated group, each with 5 cows. Melatonin‐treated cows were given subcutaneous injections of 4.64 mg melatonin (Sigma) for four consecutive days at 8:00 am based on previous study . Five control cows received the vehicle (absolute ethyl alcohol) only.…”
Section: Methodsmentioning
confidence: 99%
“…However, Auldist et al found that exogenous melatonin decreased milk yield and increased milk fat content in late lactation. Furthermore, recent studies have shown that melatonin plays important roles in regulating adipose differentiation and fat synthesis . Nevertheless, the regulatory role of melatonin in fat synthesis remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Uptake of triacylglycerol (TAG) and induction of PPAR‐γ are responsible for the switch to mitochondrial respiration and FAO . Melatonin significantly increases PPAR‐γ expression and promotes TAG accumulation via MT 2 receptor (Figure F) . Therefore, melatonin promotes M2 macrophage polarization via affecting α‐KG accumulation, FAO, and OXPHOS (Figure ).…”
Section: Mechanisms Whereby Melatonin Regulates Macrophage Polarizationmentioning
confidence: 99%